Pelatihan Pengemasan Paket Wisata dan Media Promosi Digital Bagi Pelaku Pariwisata Di Kawasan Wisata Sawarna Kabupaten Lebak Provinsi Banten - Kurnia Fajar Afgani; Yunieta Anny Nainggolan; Raden Aswin Rahadi; Asep Darmansyah; Dematria Pringgabayu; Octaviani Ratnasari Santoso; Adam Aliya Silmi; Eko Susanto; Syifaa Novianti; Chandra Budhi Septyandi; Mega Fitriani Adiwarna Prawira (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
The development of community-based tourism is an alternative approach to improving the welfare of a community. Based on this concept, community service activities are carried out to strengthen tourism management competencies for the community in the Sawarna Beach Area. The activities are carried out using off-site and on-site concepts through the application of training modules and workshops on the preparation of an electronic catalog. Pokdarwis Tanjung Layar as a partner for community service activities shows full support in the form of participating in all series of activities and providing input on packaging thematic tour packages. The results of this activity are in the form of 5 (five) electronic catalogs regarding the theme of tourism products in the Sawarna Beach Tourism Area, namely adventure, culture, nature, fishing and geoparks. This community service activity is expected to be followed up by tourism actors in the Sawarna Beach Tourism Area in order to sharpen and expand the benefits of the activities that have been carried out.